UTILIZING GOOGLE CLASSROOM AS AN ONLINE ENGLISH LEARNING MEDIA IN THE MIDDLE OF COVID-19 PANDEMIC - Faradila Putri; Eska Perdana Prasetya (LPPM Univ. Ibn Khaldun Bogor, 2021)
The world faces an exceptional worldwide wellbeing and financial emergency set off by the COVID-19 pandemic. In Indonesia, the lives of a great many youngsters and their families have just been overturned. Lockdowns and school terminations are influencing their instruction, emotional well-being and admittance to fundamental wellbeing administrations. The world of education is one that has received a change in policy due to the pandemic. To solve this problem, a solution is needed to solve it. Online learning is a solution to solving problems at the same time so that education in children continues. The purpose of this study was to determine the use of Google Classroom in English online learning in schools. The subjects of this research will be taken from eight-grade students at SMPN 16 Bogor. This data collection process will take place during online learning and is a descriptive study in which the researcher uses qualitative methods. This study concludes about the use of Google Classroom to simplify and improve the quality of teaching and learning activities in the midst of a pandemic.